Constraints Perceived by Tribal Farmers in Adoption of Recommended Practices (Indian Journal of Extension Education, 2014)
KVKs are grass root level institutions imparting training programme for the rural people. Undoubtedly training helps to improve the knowledge and skill. Therefore, the present study was undertaken during 2013-14 to identify the constraints faced by the tribal farmers in adoption of improved production technology given by Krishi Vigyan Kendra (KVK) working in the tribal district of Madhya Pradesh. The study was conducted with 225 tribal farmers (beneficiaries) randomly selected from 12 villages of Mandla, Dindori and Shahdol district. Result of the study revealed that lack of agro based and rural industries for the income generation and employment to tribals, lack of current agricultural literature, demonstrations not conducted adequately and timely, co-operative societies are not providing seeds timely, lack of storage facilities were the top most ranked constraints faced by the tribal farmers.